Efeito do ácido linoleico e catalese sobre o desenvolvimento e criotolerãncia de embriões bovinos produzidos in vitro na ausência de soro e baixa tensão de oxigênio: Mônica Ferreira Accorsi. - - Accorsi, Mônica Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The most commonly recommended way to obtain more resistant in vitro embryos during the cryopreservation process is to change these embryos, whether through removal of fetal bovine serum (FBS), addition of different supplements to the culture medium or changes in oxygen tension in the production process. The objective of this study was to assess the effects of supplementation of the culture medium with linoleic acid and/or catalase in medium without the addition of FBS, in low tension oxygen atmosphere on development, quality and cryotolerance of bovine embryos. In one group, the medium was supplemented with 100 μm of linoleic acid (LA); the second was supplemented with 100UI of catalase (CAT), a third group was supplemented with both, CAT+LA and a fourth group received no supplementation (control), during the entire culture period in an atmosphere of 5% CO2, 7% O2 and N2 88% in BAGS. Cleavage rates did not differ (P>0.05) between groups (72.7; 74.1; 72.1; and 72.0%, respectively). However, embryo production rates in D7 and D8 were different (P<0.05), where the control had the highest blastocyst rate of the treatments and the CAT+LA group presented the lowest rate of production (30.7; 22.4; 19.8; 12.4%). Expanded blastocysts were only foundon D8, indicating a delay in development. There was a significant reduction (P<0.05) of total lipids in the 3 treated groups when compared to the control group. There was no difference in the intracellular levels of ROS between the 4 groups (P>0.05).Total cell number was significantly lower (P<0.05) in the CAT+ LA and the CAT group showed the highest percentage of apoptotic cells. Considering the re-expansion rates in 24 hours (P<0.05), the control group (50%) and the CAT group (67.2%) presented lower rates than the LA group (71.7%) and CAT+LA group (76.7%). At 48 hours, the control group showed the worst rate (35.7%) followed by the CAT group (47.5%)...(Complete abstract eletronic access below)

O objetivo deste estudo foi avaliar os efeitos da suplementação do meio de cultivo com ácido linoleico e/ou catalase, em meio sem a adição de SFB, cultivados em atmosfera de baixa tensão de oxigênio sobre o desenvolvimento, qualidade e criotolerância de embriões bovinos. Em um grupo foi feita a suplementação com 100 μM de ácido linoleico (LA); 100UI de catalase (CAT) em um segundo, no terceiro grupo foram feitas as 2 suplementações (CAT+LA) e um quarto grupo sem suplementação (CONTROLE), durante todo o período de cultivo em atmosfera de 5%CO2, 7%O2 e 88%N2 em BAGS. As taxas de clivagem não diferiram (P>0,05) entre os grupos. Porém as taxas de produção de embriões em D7 e D8 diferiram (P<0,05), sendo que o controle obteve melhor resultado perante os 3 tratamentos e o grupo CAT+LA gerou a menor taxa de produção (30,7; 22,4; 19,8; 12,4%). Observou-se um atraso no desenvolvimento, sendo os blastocistos expandidos somente encontrados no D8. Na avaliação do conteúdo total de lipídios, houve uma redução significativa (P<0,05) nos 3 grupos tratados em relação ao controle. A medida dos níveis intracelulares de ROS não foi afetada nos 4 grupos (P>0,05). A quantidade de células totais foi significativamente menor (P<0,05) no grupo CAT+LA, e o grupo CAT foi o que apresentou maior porcentagem de células apoptóticas. Em relação à taxa de re-expansão às 24 horas (P<0,05), o grupo controle (50%) e o CAT (67,2%) apresentaram menores taxas que os grupos LA (71,7%) e o CAT+LA (76,7%). Às 48 horas, o grupo controle apresentou a menor taxa (35,7%), seguido pelo grupo CAT (47,5%). Já o grupo LA (56,5%) diferiu estatisticamente do controle mas não dos grupos CAT (47,5%) e CAT+LA (76,7%). O grupo CAT+LA diferiu estatisticamente dos grupos controle e CAT. Com base nestes resultados, embriões tratados com LA ou CAT+LA no cultivo in vitro, na ausêncio... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Bovino; Acidos graxos; Antioxidantes; Criopreservação; Embriologia veterinaria; Feto - Desenvolvimento; Linoleic acid